Association between genetic variants in adhesion molecules and outcomes after hematopoietic cell transplants. (30th May 2012) - Thyagarajan, B.; Jackson, S.; Basu, S.; Jacobson, P.; Gross, M. D.; Weisdorf, D. J.; Arora, M.
Summary Allogeneic hematopoietic cell transplant (HCT) is associated with a high morbidity and mortality. Adhesion molecules play an important role in endothelial activation and initiation of inflammatory response. We hypothesized that single nucleotide polymorphisms (SNPs) in the endothelial molecules may contribute to heterogeneity in HCT outcomes. We evaluated the association of 4 SNPs in ICAM1 (rs5498), PECAM1 (rs668 and rs1131012) and SELL (rs2229569) genes with acute and chronic graft‐versus‐host disease (GvHD) and those experiencing transplant‐related mortality (TRM) within 1 year among 425 allogeneic HCT recipient–donor pairs. Using a Fine and Gray proportional hazards model to evaluate the association between genetic variants and clinical outcomes, after adjustment for recipient age, race, diagnosis, disease status, gender mismatch, cytomegalovirus serostatus, gender, donor type, conditioning regimen and year of transplant, only rs5498 in the ICAM1 gene among both recipients and donors was associated with a decreased risk of TRM (P ≤ 0.02). None of the SNPs were associated with acute or chronic GvHD risk. These findings suggest that genetic variants in the vascular adhesion molecules may be used to identify patients at high risk for TRM.